A natureza jurídica dos fundos de investimento em participações - Carvalho, Cesar Augusto Rodrigues de (2019)
The main purpose of this study is to analyze the legal nature of the private equity and venture capital funds, as well as their legal framework. To this end, firstly, in order to situate such funds in the history of our capital markets and to elucidate the origin and reason of their main attributes, we will highlight the facts that leaded their initiation and evolution in the country, including the legal and practical aspects that guided their progress. We will also describe the characteristics and legal framework of such funds, by mapping the legal structures that form them, emphasizing their configuration and various particularities. We will then study the legal nature of the investment funds and, in particular, of the private equity and venture capital funds, exposing the main existing theories and legal literature on the subject, as well as making use of comparative law. Further discussions on the legal nature will allows us to explore other issues, with practical implications for private equity and venture capital funds, such as the exercising of the power of control and the liability of the quotaholders and service providers of the fund. Lastly, it will be demonstrated that the search for a better understanding of the nature and essence of the private equity and venture capital funds, as well as of their fundamental characteristics, will assist the operator of the structure to place the fund in its legal framework and to solve practical and theoretical issues which have long accompanied venture capital and private equity funds in Brazil